Fundamentals of cooperative learning, didactic strategies and the teaching of Natural Sciences (Research, Society and Development, 2020)
Cooperative learning is an instructional practice in which students perform activities in small groups, share resources and ideas in conditions of positive interdependence. It is a practice studied and evaluated in many countries, in the most diverse educational contexts: from pre-school to post-graduation, and it can be applied in the most diverse disciplines and school curricula. Contradictorily, cooperative learning is still an incipient practice in Brazil. In this work, which is strictly theoretical, a characterization of the fundamentals of cooperative learning, its conditions for implementation and the teaching strategies that are based on this practice were carried out. Surveys were made about the effectiveness of this practice in relation to others already traditionally established, such as competition and individualism. In the article, considerations about the teaching role as a guide for this practice are highlighted. At the end, we sought to associate aspects of cooperative learning in favor of a specific area: science teaching.